P10 Stimulant medication affects growth but not bone age. (7th April 2014) - Poulton, A; Evans, R; Melzer, E; Bui, Q
Abstract : Background: Children with attention deficit hyperactivity disorder (ADHD) may lose weight and grow more slowly in height in the first 3 years of treatment with stimulant medication. Whether this is associated with delay in the rate of skeletal maturation is unknown. Our aim was to investigate the effect of stimulant medication on bone age, height and weight. Methods: Prospective longitudinal study of the first 3 years of treatment with stimulant medication in children with ADHD compared with their unaffected siblings. X-rays of the non-dominant wrist and hand were taken at baseline and 3 years. The films were read independently by 2 radiologists blinded to date, age and group allocation. The bone age was calculated using Tanner and Whitehouse version 3 which uses staging of the radius, ulna and 11 small bones of the hand to compile a RUS score which is converted to bone age using gender specific reference data. Height and weight were monitored. The dose of stimulant medication (dexamphetamine or methylphenidate) was titrated with the aim of achieving the best clinical response with the lowest possible dose of medication. Groups were compared using independent samples t-tests. Correlations used Pearson's r. Results: From 2003–2009, 70 children with ADHD and 36 siblings aged 2.5–11.6 years had baseline X-rays, repeated after 3 years in 40 and 20 respectively. The correlation between the reporting of the radiologists was r = 0.96, p < 0.001. Over 3 years the ADHD children grew significantly more slowly than their sibling controls (5.2 ± 1.0 and 6.7 ± 1.2 cm/year, p < 0.0001; 2.9 ± 1.9 and 4.6 ± 2.5 kg/year, p = 0.005). The bone age progression was not significantly different between groups for either radiologist. The bone age changed by 2.90 ± 0.85 years in the subjects and 3.13 ± 1.07 years in the controls, p = 0.4 (calculated from the average of the 2 radiologists' scores). Conclusions: Despite significant differences in growth rates, the children with ADHD showed no significant delay in their rate of skeletal maturation compared to a group of healthy siblings. A slower growth rate in association with a normal rate of maturation could have adverse implications for growth potential.